A Snapshot of Chronic Critical Illness in Pediatric Intensive Care Units - Shapiro, Miriam C.; Boss, Renee D.; Donohue, Pamela K.; Weiss, Elliott M.; Madrigal, Vanessa; Henderson, Carrie M.; on behalf of the Pediatric Chronic Critical Illness Collaborative* (Journal of Pediatric Intensive Care, 2021)
Children with chronic critical illness (CCI) represent the sickest subgroup of children with medical complexity. In this article, we applied a proposed definition of pediatric CCI to assess point prevalence in medical, cardiovascular, and combined pediatric intensive care units (PICUs), screening all patients admitted to six academic medical centers in the United States on May 17, 2017, for pediatric CCI (PCCI) eligibility. We gathered descriptive data to understand medical complexity and resource needs of children with PCCI in PICUs including data regarding hospitalization characteristics, previous admissions, medical technology, and chronic multiorgan dysfunction. Descriptive statistics were used to characterize the study population and hospital data. The study cohort was divided between PICU-prolonged (stay > 14 days) and PICU-exposed (any time in PICU); comparative analyses were conducted. On the study day, 185 children met inclusion criteria, 66 (36%) PICU-prolonged and 119 (64%) PICU-exposed. Nearly all had home medical technology and most (n = 152; 82%) required mechanical ventilation in the PICU. The PICU-exposed cohort mirrored the PICU-prolonged with a few exceptions as follows: they were older, had fewer procedures and surgeries, and had more recurrent hospitalizations. Most (n = 44; 66%) of the PICU-prolonged cohort had never been discharged home. Children with PCCI were a sizable proportion of the unit census on the study day. We found that children with PCCI are a prevalent population in PICUs. Dividing the cohorts between PICU-prolonged and PICU-exposed helps to better understand the care needs of the PCCI population. Identifying and studying PCCI, including variables relevant to PICU-prolonged and PICU-exposed, could inform changes to PICU care models and training programs to better enable PICUs to meet their unique needs.
Keywords: chronic critical illness; pediatrics; intensive care